2022
DOI: 10.1177/19714009221083145
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the use of proton magnetic resonance spectroscopy in distinguishing between primary and secondary malignant tumors of the central nervous system

Abstract: Background and purpose Conventional magnetic resonance images (MRI) has limitations in distinguishing primary from secondary brain tumors. Proton magnetic resonance spectroscopy ( 1 H-MRS) allows evaluation of the concentration of metabolites in a brain lesion and, hence, better characterization of the tumor. Considering that an accurate diagnosis determines the choice of treatment, our purpose was to assess the usefulness of spectroscopy data for differentiating between primary and secondary brain neoplasms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, this association may not be present in high-grade gliomas characterized by extensive necrosis, which tend to result in a low choline peak. In such cases, increased lactate and lipid concentrations typically suppress the peaks of other metabolites, including Cho [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…However, this association may not be present in high-grade gliomas characterized by extensive necrosis, which tend to result in a low choline peak. In such cases, increased lactate and lipid concentrations typically suppress the peaks of other metabolites, including Cho [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis has revealed that there may be similarities between the metabolite levels of different grade gliomas; for example, the rise in creatine may be similar, while the level of creatine in metastatic tumors may be lower. 28–30 …”
Section: Discussionmentioning
confidence: 99%
“…Analysis has revealed that there may be similarities between the metabolite levels of different grade gliomas; for example, the rise in creatine may be similar, while the level of creatine in metastatic tumors may be lower. [28][29][30] Gliosarcoma can also be differentiated from lymphoma since the signals they produce in plain and enhanced scans differ, and circular enhancement is rare for lymphoma. Lymphoma predominantly exhibits hypointensity or isointensity on T 1 WI and T 2 WI, and clear and intense enhancement can be observed following contrasting.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…61 MRI and 1 H-MRS images of patients with histologically confirmed BTs. [39] CCA might help to distinguish PsP or RN from PD after RT. 16 patients with a primary and 17 with a secondary BT.…”
Section: Mrimentioning
confidence: 99%